SAT0228 Efficacy of Rituximab for The Treatment of Interstitial Lung Disease Associated with Connective Tissue Diseases – A Retrospective Analysis. (15th July 2016) - Jethwa, H.; Patel, I.; Steuer, A.; Demetriadi, F.; Power, S.; Adler, M.; Lloyd, M.; Pretsell, E.
Abstract : Background: Interstitial lung disease (ILD) is a notable complication of Connective Tissue Diseases (CTDs) characterised by lung inflammation and scarring, leading to a reduced functional capacity, shortness of breath and exercise-induced hypoxia. To date, the mainstay of treatment for this condition is Cyclophosphamide (CYC); some patients, however, fail to respond and recent reports have shown that Rituximab may be beneficial as a second-line option. Currently, no guidelines are available to direct the management of CYC-resistant patients and, at present, these individuals remain to be treated on a case-by-case basis. Objectives: To retrospectively evaluate the efficacy of Rituximab treatment in patients with ILD associated with CTDs. Methods: We retrospectively reviewed patients in our trust with CTD associated ILD, refractory to cyclophosphamide, in whom Rituximab has been used. Parameters assessed were lung function (forced vital capacity (FVC) and carbon monoxide transfer factor (TLCO)), radiographic changes and creatine kinase (CK) response (for myositis) both pre- and post-treatment. Results: Our cohort included 7 patients (4 females, 3 males) – average age 42 years. 6 patients had underlying diagnosis of polymyositis (3 anti-Jo, 2 anti-Jo/Ro, 1 anti-Zo) and 1 had an undifferentiated CTD. Average disease duration of 70 months. On high resolution CT scan, 3 patients had non-specific interstitial pneumonia (NSIP) pattern, 2 had usual interstitial pneumonia (UIP), 1 organising pneumonia, and one had features of both cryptogenic pneumonia and NSIP. Of note, one patient had mild co-existant pulmonary arterial hypertension. Previous treatments included CYC, azathioprine and steroids. Lung function results were available for 6 of 7 patients – 5 of these patients showed improvement in post-treatment FVC and TLCO (average improvement 11.2% predicted; 0.14L and 4.06% predicted, respectively). Two patients had CT scans following treatment – one showed no change from baseline scan, and one (who later died of disease progression) showed worsened fibrosis. Regarding muscle involvement, 5 of 7 patients had pre-treatment CK values available – two of these patients had a normal CK prior to Rituximab treatment. Interestingly, in the 3 patients with elevated CK levels, an average 45.3% improvement in CK was noted following Rituximab therapy. Conclusions: This study reports improvement in both lung function tests and CK response in the majority of a small cohort of patients with CTD associated ILD following Rituximab treatment. Similar results have been shown in other small cohort studies. Larger, randomised studies are needed to further assess the response to Rituximab therapy and determine whether these findings have statistical significance. Consideration of a formal treatment pathway for patients resistant to CYC treatment would be helpful on both a local and national level to determine which patients are likely to have poor response to CYC, when to trial Rituximab and to determine markers of response to Rituximab treatment, including patient reported outcomes. References: Kier et al. Severe interstitial lung disease in connective tissue disease: rituximab as rescue therapy. The European Respiratory Journal 2012; 40(3): 641–8. Disclosure of Interest: None declared